Anger or emotional upset and heavy physical exertion as triggers of stroke: the INTERSTROKE study. (1st December 2021) - Smyth, Andrew; O'Donnell, Martin; Hankey, Graeme J; Rangarajan, Sumathy; Lopez-Jaramillo, Patricio; Xavier, Denis; Zhang, Hongye; Canavan, Michelle; Damasceno, Albertino; Langhorne, Peter; Avezum, Alvaro; Pogosova, Nana; et al.
Abstract: Aims: In INTERSTROKE, we explored the association of anger or emotional upset and heavy physical exertion with acute stroke, to determine the importance of triggers in a large, international population. Methods and results: INTERSTROKE was a case–control study of first stroke in 32 countries. Using 13 462 cases of acute stroke we adopted a case-crossover approach to determine whether a trigger within 1 hour of symptom onset (case period), vs. the same time on the previous day (control period), was associated with acute stroke. A total of 9.2% ( n = 1233) were angry or emotional upset and 5.3% ( n = 708) engaged in heavy physical exertion during the case period. Anger or emotional upset in the case period was associated with increased odds of all stroke [odds ratio (OR) 1.37, 99% confidence interval (CI), 1.15–1.64], ischaemic stroke (OR 1.22, 99% CI, 1.00–1.49), and intracerebral haemorrhage (ICH) (OR 2.05, 99% CI 1.40–2.99). Heavy physical exertion in the case period was associated with increased odds of ICH (OR 1.62, 99% CI 1.03–2.55) but not with all stroke or ischaemic stroke. There was no modifying effect by region, prior cardiovascular disease, risk factors, cardiovascular medications, time, or day of symptom onset. Compared with exposure to neither trigger during the control period, the odds of stroke associated with exposure to both triggers were not additive. Conclusion: Acute anger or emotional upset was associated with the onset of all stroke, ischaemic stroke, and ICH, while acute heavy physical exertion was associated with ICH only. Graphical Abstract: